Förster resonance energy transfer (FRET) between heterogeneously distributed probes: application to lipid nanodomains and pores - Šachl, Radek; Johansson, Lennart B-Å; Hof, Martin (International journal of molecular sciences, 2012)
The formation of membrane heterogeneities, e.g., lipid domains and pores, leads to a redistribution of donor (D) and acceptor (A) molecules according to their affinity to the structures formed and the remaining bilayer. If such changes sufficiently influence the Förster resonance energy transfer (FRET) efficiency, these changes can be further analyzed in terms of nanodomain/pore size. This paper is a continuation of previous work on this theme. In particular, it is demonstrated how FRET experiments should be planned and how data should be analyzed in order to achieve the best possible resolution. The limiting resolution of domains and pores are discussed simultaneously, in order to enable direct comparison. It appears that choice of suitable donor/acceptor pairs is the most crucial step in the design of experiments. For instance, it is recommended to use DA pairs, which exhibit an increased affinity to pores (i.e., partition coefficients K(D,A) > 10) for the determination of pore sizes with radii comparable to the Förster radius R(0). On the other hand, donors and acceptors exhibiting a high affinity to different phases are better suited for the determination of domain sizes. The experimental setup where donors and acceptors are excluded from the domains/pores should be avoided.
Keywords: rezonanční přenos fluorescenční energie; fluorescenční barviva; membránové mikrodomény; tkáňová distribuce; Ion Channels; Lipid Bilayers; Fluorescence Resonance Energy Transfer; teoretické modely; Fluorescent Dyes; lipidové dvojvrstvy; Models, Theoretical; iontové kanály; Monte Carlo Method; Membrane Microdomains; Tissue Distribution; metoda Monte Carlo